Effects of solar radiation on photosynthetic physiology of barren stalk differentiation in maize. (November 2021) - Feng, Ying; Cui, Xue; Shan, Hong; Shi, Zhensheng; Li, Fenghai; Wang, Hongwei; Zhu, Min; Zhong, Xuemei
Highlights: Weak light can accelerate the senescence process of maize, which is accompanied by the production of ROS. Weak light destroyed the balance of free radical production and scavenging, causing mesophyll cells and chloroplasts damage. Compared with SN98A, SN98B has a stronger ability to remove ROS and maintain the stability of the photosynthetic system. Self-protection mechanism is an important physiological reason for its adaptation to weak light. Abstract: Barren stalks and kernel abortion are the major obstacles that hinder maize production. After many years of inbreeding, our group produced a pair of barren stalk/non-barren stalk near-isogenic lines SN98A/SN98B. Under weak light stress, the barren stalk rate is up to 98 % in SN98A but zero in SN98B. Therefore, we consider that SN98A is a weak light-sensitive inbred line whereas SN98B is insensitive. In the present study, the near-isogenic lines SN98A/SN98B were used as test materials to conduct cytological and photosynthetic physiological analyses of the physiological mechanism associated with the differences in maize barren stalk induced by weak light stress. The results showed that weak light stress increased the accumulation of reactive oxygen species (ROS), decreased the function of chloroplasts, destroyed the normal rosette structure, inhibited photosynthetic electron transport, and enhanced lipid peroxidation. The actual photochemical quantum efficiency for PSI (Y(I)) and PSII (Y(II)), relative electron transfer rate for PSI (ETR(I)) and PSII (ETR(II)), and the P700 activities decreased significantly in the leaves of SN98A and SN98B under weak light stress, where the decreases were greater in SN98A than SN98B. After 10 days of shading treatment, the O2 ·– production rate, H2 O2 contents, the yield of regulated energy dissipation (Y(NPQ)), the donor side restriction for PSI (Y(ND)) and the quantum efficiency of cyclic electron flow photochemistry were always higher in SN98A than SN98B, and the antioxidant enzyme activities were always lower in SN98A than those in SN98B. These results show that SN98B has a stronger ability to remove ROS at its source, and maintain the integrity of the structure and function of the photosynthetic system. This self-protection mechanism is an important physiological reason for its adaptation to weak light.